Videos as partners in ESP and technical terminology teaching: profiling an international joint project - Vasconcelos, Sandra (2021)
Focusing on the use of digital technology to promote the teaching of English for Specific Purposes (ESP) in Higher Education, this paper documents the preliminary stages of an international joint project involving students and faculty from Lithuania, Portugal and Serbia. Part of a long-term study, and stemming from the need to re-examine current teaching methods within the scope of technical terminology and ESP, this project aims at understanding the role digital technology, and particularly video, can play in enhancing students’ learning experiences in ESP in areas such as Information Technologies, Management, Law, and Translation. Based on the available preliminary data, this paper is divided into three different sections. After establishing the rationale behind the project’s development and providing a framework to support its application, the authors describe the first stage of implementation, outlining the activities that have taken place thus far and drawing the participants’ profile, analysing their perceptions regarding the use of digital technology and videos in language learning and the role they can play in enhancing engagement and creativity. Despite the project’s experimental nature and the fact that it is at a very early stage of development, the initial data suggest that, even though students are divided on whether the use of technology can disrupt classroom learning, overall, they are motivated to use digital devices for learning and consider that videos can be useful for learning English and technical terminology. The data also seem to support that the use of digital technology, and particularly videos, have the potential of making allowances for the production of collaborative outputs that require students to apply specific terminology within the scope of their fields, while solving activities by using creative approaches.